Penyelesaian sengketa Kepailitan Menurut Hukum Perbankan Syariah - Erna Widjajati (Universitas Islam Negeri Jakarta, 2015)
Based UUPA No: 3 of 2006 related to its jurisdiction to examine cases of economic disputes sharia and based PERMA No.2 Year 2008 concerning Law Compilation of Islamic Economics was decided by the Supreme Court refers to the Law No: 27 of 2004 pointed to the Commercial Court. Though Religious of Court that have the authority dispute bankruptcy contains elements of Islamic economics, including Islamic banking. In Bankruptcy Decision No: 7/Pailit / 2011/PU. Commerce JKT PST strengthened MARI Decision No: 346 F/PDT.SUS/2011 did not consider the existence of PERMA No: 2 of 2008 on the specified Economics Law Compilation Supreme Court.DOI: 10.15408/ajis.v15i1.2855